2020
DOI: 10.1007/s11205-020-02387-8
|View full text |Cite
|
Sign up to set email alerts
|

Food Insecurity in Europe: A Gender Perspective

Abstract: Food insecurity is the limited or uncertain availability of nutritionally adequate and safe foods or limited or uncertain ability to acquire foods in socially acceptable ways. The study presents a comparison of the principal determinants of individual food insecurity in Europe and other Continents, with particular regard to gender, since the literature clearly states the importance of women in the administration of food in the household. The study of gender related differences in food insecurity is particularl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
52
2
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(68 citation statements)
references
References 28 publications
10
52
2
4
Order By: Relevance
“…Our results also confirm the inverted U-shape relationship between the age of the respondent and the prevalence of FI reported for upper middle-income and high-income countries [ 15 , 19 , 52 ]. In line with previous studies [ 19 , 22 , 53 ], our results confirm the role of education as an extremely important factor against FI. Moreover, it was found that usually unemployed individuals were the most vulnerable to FI.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Our results also confirm the inverted U-shape relationship between the age of the respondent and the prevalence of FI reported for upper middle-income and high-income countries [ 15 , 19 , 52 ]. In line with previous studies [ 19 , 22 , 53 ], our results confirm the role of education as an extremely important factor against FI. Moreover, it was found that usually unemployed individuals were the most vulnerable to FI.…”
Section: Discussionsupporting
confidence: 93%
“…However, unlike the above research, our results indicate that singles were not more affected by FI than married respondents. This is in line with results of Grimaccia and Naccarato [ 22 ], showing that in Eastern Europe the difference between these two groups was not significant at 0.05. Considering the observed inverted U-shape relationship between the age of the respondents and FI, our results can be largely explained by the age of respondents, as the average age in the never married group was 27, while in the married respondents group it was 50.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations